KEABSAHAN PENANDATANGANAN APBD OLEH PELAKSANA HARIAN SEKRETARIS DAERAH PROVINSI JAWA TIMUR - Mohammad Ashari (Fakultas Hukum Universitas Narotama, 2022)
The government must find a solution to solve the problem of vacancies. To anticipate the ineffectiveness of public services and state administration, there must be a state apparatus that carries out the duties and functions of the position left by the incumbent. The filling of vacancies can be done by filling certain public officials with the existing state apparatus. The position can be assigned according to existing rules or laws so that government services can continue to run. The filling of vacancies can be done by appointment or delegation in accordance with the needs and laws and regulations. in accordance with applicable laws and regulations, other public officials may fill vacant positions in the form of Daily Executive Officers, hereinafter referred to as (Plh) and Acting Officers, hereinafter referred to as (Plt). In this case, the author uses a normative juridical approach. In addition, in the writing of this research, a legal concept analysis approach, analysis of legislation, and a case approach related to the position occupied by Heru Tjahjono as the Daily Executive Secretary of the East Java Regional Government was used. Meanwhile, in collecting the data, the writer uses the method of collecting data through document/library studies (library research). The results of this study indicate that the authority of the Acting Regional Secretary, in this case the Regional Secretary of the East Java Province, is indeed limited to matters of a strategic nature because the day-to-day executive officers are only a continuation of the wheels of the Regional Government. If during that time a strategic policy is needed that must be taken by the Acting Secretary of the East Java Province, then Article 132 A paragraph (1) of PP 49/2008 can be used as the basis for taking strategic policies. However, according to paragraph (2) of the provisions of this article, it is stated that these 4 (four) prohibitions can be excluded after obtaining written approval or permission from the Minister of Home Affairs. Keywords: Authority, Daily Executor, and Provincial Secretary.